2008
DOI: 10.1021/jo8020264
|View full text |Cite
|
Sign up to set email alerts
|

Total Synthesis of Azumamide E and Sugar Amino Acid-Containing Analogue

Abstract: An efficient and practical total synthesis of marine cyclic tetrapeptide, natural product azumamide E (1) is achieved via high-yielding reactions. The strategy also allowed us to synthesize the azumamide E-SAA (sugar amino acid) analogue (2), whose solution-phase NMR and biological activity studies were also carried out.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(21 citation statements)
references
References 27 publications
0
21
0
Order By: Relevance
“…Azumamide E, one of the most potent of the azumamides, also showed roughly 100-fold selectivity for class I over class II HDACs (HDAC1–3, IC 50 = 50–100 nM versus HDAC4–7, 9, IC 50 = 9.7–28 μM) [94]. Chandrasekhar et al [95] reported the total synthesis of azumamide E and sugar amino acid-containing analog (azumamide E-SAA) 3 . A near total inhibition of HDAC activity in a cell-free system was achieved by 20 μM of compound 3 .…”
Section: Review Of Macrocyclic Hdacimentioning
confidence: 99%
“…Azumamide E, one of the most potent of the azumamides, also showed roughly 100-fold selectivity for class I over class II HDACs (HDAC1–3, IC 50 = 50–100 nM versus HDAC4–7, 9, IC 50 = 9.7–28 μM) [94]. Chandrasekhar et al [95] reported the total synthesis of azumamide E and sugar amino acid-containing analog (azumamide E-SAA) 3 . A near total inhibition of HDAC activity in a cell-free system was achieved by 20 μM of compound 3 .…”
Section: Review Of Macrocyclic Hdacimentioning
confidence: 99%
“…1) and their homooligomers are part of several bioactive macromolecules (Gruner et al 2001(Gruner et al , 2002aChandrasekhar et al 2009). Among them, H-RibAFU(ip)-OH, (1a) (Gruner et al 2002b) and its xylo epimer H-XylAFU(ip)-OH (2a) (Chandrasekhar et al 2004) as hydrophilic analogs of cisand trans-ACPC monomers were incorporated into β-peptidic heterooligomers.…”
Section: Introductionmentioning
confidence: 99%
“…16,17 The unusual norbornane amino acid was synthesized as reported in the literature using commercially available norbornene. [16][17][18][19][20] The synthesis was performed in two pathways: (i) synthesis of dimers and tetramer (ii) synthesis of hexamer followed by Yamaguchi macrocyclization. [21][22][23] (S)-Phenylalanine amine salt (1) in DCM solution is neutralized with TEA at 0°C to get (S)-methyl 2-amino-3-phenyl propionate (2).…”
Section: Results and Discussion: Chemistrymentioning
confidence: 99%